A realist evaluation to identify targets to improve the organization of compression therapy for deep venous thrombosis- and chronic venous disease patients. - Rachel H P Schreurs; Manuela A Joore; Daisy P De Bruijn-Geraets; Hugo Ten Cate; Arina J Ten Cate-Hoek (PLoS ONE, 2022)
Background Although compression therapy is well established for patients with deep venous thrombosis (DVT) and chronic venous disease (CVD), considerable variation exists in its organization in clinical practice which may impact patient outcomes. The current study aims to deepen our understanding of the main drivers of the complex care organization for compression therapy and to identify targets for improvement. Methods This realist evaluation includes a mixed-method design consisting of semi-structured interviews with patients and health care professionals involved in compression therapy (n = 30), stakeholder meetings (n = 2) and surveys (n = 114). Data were collected to create the content of context-mechanism-outcome-configurations (CMOcs) important in compression therapy. Based on these CMOcs, targets for improvement to optimize the organization of compression care were identified. Results We identified overarching context factors and mechanisms targeting four optimal outcomes for the organization of compression therapy: selecting initial compression therapy types that support patient's self-reliance (1), evidence based selection of elastic compression stocking type and class (2), patient-based selection of assistive devices (3), individualizing treatment duration for DVT patients (4a) and providing follow-up for CVD patients (4b). We found that increasing health care professionals' knowledge of compression therapy, the availability of unambiguous protocols and guidelines, increasing patient involvement (and if applicable their informal care giver) in the decision making process, the accessible availability of resources, and increasing interdisciplinary consultation enhanced desirable outcomes. These targets triggered mechanisms such as increased health care professionals' willingness, confidence and motivation to provide patient-based care and increased patients' self-confidence and self-efficacy. Conclusions This study provides a detailed insight into what needs to be in place to optimize compression care and identified five main targets for improvement.